Efektivitas “Portable UV Disinfection” dalam Menurunkan Angka Bakteri (Escherichia Coli Spp) pada Air Minum - Syarifudin A.; Zulfikar Ali As; Gunung Setiadi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2014)
Abstrak: Effectivity of “Portable UV Disinfection” to Decrease Bacterial Number (Escherichia Coli Spp) in Drinking Water. Disinfection using ultraviolet ray is faster, more accurate and chiefer. This research aims to measure the effectivity of portable UV disinfection to decrease bacterial number (E. Coli) in drinking water. This research used true experiment methods with postest only control group design on laboratory scale. Drinking water contained E. Coli taken from wheel then disinfected by ultraviolet ray. Variation of treatment included variation of water depth 10, 15, dan 20 cm and variation of detention time 0, 1, 5, 10, dan 20 minutes. The result show ultraviolet ray been able to kill E. Coli in drinking water. Removal efficiency of E. Coli at 10 cm water depth with 0, 1, 5, 10, and 20 minutes detention time were 0,0%, 75,0%, 76,2%, 98,0%, and 98,3% particularly. At 15 cm water depth, removal efficiency of E. Coli were 0,0%, 36,3%, 58,2%, 68,0%, dan 89,0% particularly. At 20 cm water depth, removal efficiency of E. Coli were 0,0%, 56,1%, 77,5%, 83,9%, dan 88,1% particularly. Statistical test showed the number of killed bacteria based on detention time was difference significantly. The longer time to be flashed the killed bacterial more. Flash of ultraviolet ray with lumination be able to kill the bacterial more effective.Key Words : Portable UV Disinfection;  E. Coli;  drinking water